DOP032 Extracellular vesicles from Bifidobacterium longum Subspecies infantis attenuate intestinal inflammation via macrophage polarization - H J Jeon; S Seo; H S Lee; S H Kim; J Park; S E Kim; S A Jung; C M Moon (Journal of Crohn's and Colitis, 2025)
Abstract Background Inflammatory Bowel Disease (IBD) is characterized by chronic intestinal inflammation driven by a complex interplay of genetic, environmental, and immune interactions1. Despite significant advancements in IBD therapies, many patients still face challenges in achieving complete remission or maintaining long-term treatment efficacy. We hypothesize that extracellular vesicles from Bifidobacterium longum subspecies infantis (B. infantis-EVs) can regulate immune responses, promote balanced macrophage polarization, and modulate the gut microbiota, ultimately attenuating intestinal inflammation. Methods B. infantis-EVs were isolated via tangential flow filtration (TFF)2. In vitro studies examined cellular morphology, expression of inflammatory cytokines, and immunofluorescence staining of activated RAW 264.7 macrophage cells34. In a 3% dextran sulfate sodium (DSS) mouse model, disease severity was assessed using the Disease Activity Index (DAI), colon length, survival rate, and metagenome analysis. To confirm the targeting capability of B. infantis-EVs for inflamed lesions, cellular uptake was analyzed using confocal microscopy, and biodistribution was assessed with an In Vivo Imaging System (IVIS). Results To investigate the effects of B. infantis-EVs on macrophage polarization, we examined the cellular morphology and macrophage markers of RAW 264.7 cells. B. infantis-EVs suppress macrophage cells from driving an M1-like phenotype, and downregulated M1 markers (iNOS and CD86) while upregulating M2 markers (Arg1 and CD200R) (Fig. 1a-c). They also decreased the expression of LPS-induced pro-inflammatory cytokines (IL-1β, IL-2, IL-6, and TNF-α) while increasing anti-inflammatory cytokines (IL-10 and TGF-β) (Fig. 1d). In vivo, oral administration of B. infantis-EVs mitigated weight loss (p=0.0120), preserved colon length (p=0.0018), reduced DAI (p=0.0079), lowered histological score (p=0.0003), and modulated gut microbiota composition in DSS-treated mice compared to the DSS + PBS groups. Additionally, fluorescence intensities were stronger in the inflamed group treated with Cy5-labeled B. infantis-EVs compared to non-inflamed group at all-time points tested both cellular uptake and biodistribution (Fig. 1e). These findings suggest that B. infantis-EVs have the capability to target inflamed lesions and exhibit significant anti-inflammatory effects. Conclusion In this study, B. infantis-EVs attenuated intestinal inflammation via the modulation of macrophage polarization with its targeting capability to inflamed lesions. B. infantis-EVs could emerge as an innovative and promising therapeutic option for future IBD treatment. References 1. Guan Q. A Comprehensive Review and Update on the Pathogenesis of Inflammatory Bowel Disease. Journal of Immunology Research. 2019;2019(1):1-16. doi:https://doi.org/10.1155/2019/7247238 2. You DG, Lim GT, Kwon S, et al. Metabolically engineered stem cell–derived exosomes to regulate macrophage heterogeneity in rheumatoid arthritis. Science Advances. 2021;7(23). doi:https://doi.org/10.1126/sciadv.abe00832. 3. Choi JH, Moon CM, Shin TS, et al. Lactobacillus paracasei-derived extracellular vesicles attenuate the intestinal inflammatory response by augmenting the endoplasmic reticulum stress pathway. Experimental & Molecular Medicine. 2020;52(3):423-437. doi:https://doi.org/10.1038/s12276-019-0359-33. 4. Lee Y, Sugihara K, Gillilland MG, Jon S, Kamada N, Moon JJ. Hyaluronic acid–bilirubin nanomedicine for targeted modulation of dysregulated intestinal barrier, microbiome and immune responses in colitis. Nature Materials. Published online August 19, 2019. doi:https://doi.org/10.1038/s41563-019-0462-